An assessment of outcomes of the nutritional supplementation programme of children at Prince Mshiyeni memorial hospital, Umlazi, Kwazulu Natal - Stephen, Neil Robert (My University, 2015)
Aim: Malnutrition, specifically undernutrition, contributes to a reduction in potential for childhood growth and development, and an increase in morbidity and mortality. This study seeks to investigate whether sufficient weight gain is achieved using the existing nutrition supplementation programme offered by the Dietetics Department at Prince Mshiyeni Memorial Hospital. Methods: A retrospective descriptive study with analytical components was undertaken. Data from children receiving nutritional supplementation was extracted from an existing database belonging to the Dietetics Department. Factors influencing weight for length/ height (WL/HZ) and BMI for age z-scores (BMIAZ), and the change in anthropometric indicators, social factors, food security, reported symptoms and nutrition risk score were analysed for significance. Results: All Anthropometric indicators, except length/height for age z-scores (L/HAZ), showed positive significant (p<0.001) change over the first month of being in the programme. Between baseline and month six, significant positive changes were found for weight for age z-score (WAZ) (p<0.001), WL/HZ (p=0.004), and BMIAZ (p=0.028). It is clear the programme had a significant influence on BMIAZ and WL/HZ over time, p<0.001 from baseline to month one, and p<0.01 for baseline to month six. There were no significant changes in social factors. Food gardens (p=0.001) and patients receiving supplements from the PEM scheme (p=0.002) increase significantly over the duration of 6 months. The nutrition risk score and most symptoms (except vomiting) presenting at baseline decreased significantly over time, but most significantly in the first month (p<0.002). It is evident that tuberculosis (TB) significantly delayed patient outcomes of BMIAZ >-1z-score (p=0.02) and WL/HZ (p=0.04) within 6 months of nutritional treatment. There is also a positive effect (p=0.04) on WL/HZ outcome if the patient was already receiving supplements on the PEM scheme. Conclusion: The Prince Mshiyeni nutrition programme (PNP) targeted and had a positive effect on BMIAZ and WL/HZ outcomes of the malnourished children entered. There was a significant improvement in WAZ, WL/HZ, BMIAZ, and symptoms affecting nutrition over time. Food gardens and the number of patients accessing the PEM scheme increased significantly over the duration of the programme. The presence of TB hindered anthropometric outcomes significantly. The PEM scheme should be strengthened at clinics by improving service delivery to encourage patients to use clinics. The clinics will benefit from hospital level dietitians supporting their nutrition services. The importance of nutrition and adherence to treatment must be emphasised in TB programmes specifically in children. Food gardens should be emphasised in nutrition programmes at all levels of care. Seeds could be issued along with patient education on food gardening. Access to child support grants must be improved. Further research is required on TB, TB treatment adherence, and the possible effect on nutrition status, why patients have not accessed the PEM scheme at clinics, why patients have not accessed CSG’s from birth, and how food gardens could contribute significantly to food security. The PNP programme has positively affected anthropometric outcomes of patients, and this study exposes, and provides possible solutions to the challenges presented.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Science (Medicine) in the field of Community Paediatrics Johannesburg 2015
Keywords: Malnutrition